A Simple Tenckhoff Catheter Placement Technique for Continuous Ambulatory Peritoneal Dialysis (CAPD) Using the Bandung Method - Jonny; Rudi Supriyadi; Rully Roesli; Goh Bak Leong; Lydia Permata Hilman; Fidelisa Cita Arini (International Journal of Nephrology)
Insertion of Tenckhoff catheters for continuous ambulatory peritoneal dialysis by nephrologists remains uncommon in most developing countries, including Indonesia. The aim of this study is to describe our experience on a simple technique of Tenckhoff catheter insertion by a nephrologist called the Bandung method. We conducted a retrospective observational study from May 2012 until December 2018 in 230 patients with end-stage renal disease using the Bandung method, a blind percutaneous insertion approach modified from the Seldinger technique. Early complications after insertion were assessed. The mean age of patients was 47.28 years (range 14–84 years). Within 1 month after insertion, complications occurred in 34 patients: 13 (5.7%) malposition, 8 (3.5%) omental trapping, 6 (2.6%) outlow failure, 3 (1.3%) peritonitis, 1 (0.4%) catheter infections, 1 (0.4%) bleeding, 1 (0.4%) kinking, and 1 (0.4%) hernia. None of these complications led to catheter removal. One patient experienced a late (>1 month) post-insertion complication of malposition that could not be repositioned and led to catheter removal. The Bandung method is a simple, cost effective, and minimally invasive technique for Tenckhoff catheter insertion that is associated with the same rate of complications compared to other techniques. This technique may useful for application in developing countries.